Governing Without Government: Nonprofit Governance in Detroit and Flint. Issue 5 (September 2020) - Reckhow, Sarah; Downey, Davia; Sapotichne, Joshua
Scholars across the social sciences have shown how economic, social, and political changes are weakening local governments and contributing to rising nonprofit activity in urban politics. But these trends could now add up to a new form of decision-making in some American cities. The convergence of public sector austerity and a burgeoning philanthropic and nonprofit sector have created space for what we call "nonprofit governance." In some cities, nonprofit leaders can guide urban policy, sometimes with limited input from elected officials or citizens. First, we apply insights from studies in comparative politics to demonstrate how nonprofit leadership can expand, particularly in the context of a weak state. Next, we assess trends in public sector capacity, based on local government employment in Midwestern U.S. cities. We closely examine Detroit and Flint due to dramatic declines in local government capacity and recent public sector crises in both cities, focusing on the role of nonprofits in each. These leading-edge cases allow us to trace the development of nonprofit governance and explore different forms of nonprofit and local government relationships.